Regional development programmes and poverty reduction in East Coast states of Malaysia - Mohd Noor, Zaleha; Asfari, Noor Azian (Universiti Putra Malaysia Press, 2013)
Regional disparities can be found in Malaysia. The Central Region can be considered as a developed region; while Sabah and the states in the Eastern Region,the least developed. Such disparities exist not only in the form of income, but also in terms of social welfare. It is then important to highlight the problems related to poverty in the poorer states of Malaysia. Many regional programs which involve a lot of resources have been carried out in every Malaysian plan. One of its aims is to eradicate poverty among the poor. In the same vein, the objective of this paper is to analyze the implication of regional development programs in reducing poverty. This paper made use of the Household Income Survey (HIS) for 1999 and 2004 data to calculate the relevant indexes to trace the changes in poverty incidence, extent and severity. These indexes include the head-count index, poverty gap and income-gap ratio, Sen’s index of poverty, as well as the Foster, Greer and Thorbecke (FGT) index. Results revealed that the regional programs conducted between the two periods improved poverty situations in the region; thus, such programs should be continued to increase the economic performance of the so-called poor states of Kelantan, Terengganu and Pahang and reduce their poverty situation.